A Novel Protective Vaccine Antigen from the Core Escherichia coli Genome - Danilo G. Moriel (American Society for Microbiology, 2016)
ABSTRACT Escherichia coli is a versatile pathogen capable of causing intestinal and extraintestinal infections that result in a huge burden of global human disease. The diversity of E. coli is reflected by its multiple different pathotypes and mosaic genome composition. E. coli strains are also a major driver of antibiotic resistance, emphasizing the urgent need for new treatment and prevention measures. Here, we used a large data set comprising 1,700 draft and complete genomes to define the core and accessory genome of E. coli and demonstrated the overlapping relationship between strains from different pathotypes. In combination with proteomic investigation, this analysis revealed core genes that encode surface-exposed or secreted proteins that represent potential broad-coverage vaccine antigens. One of these antigens, YncE, was characterized as a conserved immunogenic antigen able to protect against acute systemic infection in mice after vaccination. Overall, this work provides a genomic blueprint for future analyses of conserved and accessory E. coli genes. The work also identified YncE as a novel antigen that could be exploited in the development of a vaccine against all pathogenic E. coli strains—an important direction given the high global incidence of infections caused by multidrug-resistant strains for which there are few effective antibiotics. IMPORTANCE E. coli is a multifaceted pathogen of major significance to global human health and an important contributor to increasing antibiotic resistance. Given the paucity of therapies still effective against multidrug-resistant pathogenic E. coli strains, novel treatment and prevention strategies are urgently required. In this study, we defined the core and accessory components of the E. coli genome by examining a large collection of draft and completely sequenced strains available from public databases. This data set was mined by employing a reverse-vaccinology approach in combination with proteomics to identify putative broadly protective vaccine antigens. One such antigen was identified that was highly immunogenic and induced protection in a mouse model of bacteremia. Overall, our study provides a genomic and proteomic framework for the selection of novel vaccine antigens that could mediate broad protection against pathogenic E. coli.